Occurrence of Similar Periods in Geomagnetic Field Variations and Solar Activity - Rabiu, A. B.; Abdulrahim, R. B.; Garuba, O. A.; Adekanmbi, O. O.; Alabi, S. A.; Ojurongbe, L. L.; Lawani, A. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The periodicities associated with some geomagnetic field parameters under quiet and disturbed solar conditions have been examined using a set of data spanning through five years obtained courtesy of INTERMAGNET network. Hourly values of the Horizontal component of the geomagnetic field simultaneously obtained at seven INTERMAGNET stations were engaged in the study. The stations were well distributed across the latitudes, viz: Bangui, 4.4°N; Kourou, 5.1°N; Alibag, 18.6°N; San Juan18.1°N; Crozet, 46.4°S; Barrow, 71.3°N; Scott Base, 77.9°S). Solar quiet daily variation Sq, Superposed Magnetic field SPMF and Solar disturbance daily variation SD in the horizontal magnetic field component were evaluated and studied for their spectral characteristics. The spectral analysis revealed the periods of 6 hours, 12 hours, 24 hours, 3 months, 6 months, 12 months and 16 months in the geomagnetic field variations. The observed periodicities were explained in terms of associated solar terrestrial processes. This clearly shows the influence of an extra terrestrial source (the Sun) on terrestrial processes. Sun is the undisputable driver of space weather